2019
DOI: 10.3390/met9050608
|View full text |Cite
|
Sign up to set email alerts
|

Wire and Arc Additive Manufacturing of Aluminum Components

Abstract: An increasing demand for flexibility and product integration, combined with reduced product development cycles, leads to continuous development of new manufacturing technologies such as additive manufacturing. Wire and arc additive manufacturing (WAAM) provides promising technology for the near net-shape production of large structures with complex geometry, using cost efficient production resources such as arc welding technology and wire materials. Compared to powder-based additive manufacturing processes, WAA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(48 citation statements)
references
References 11 publications
3
44
0
1
Order By: Relevance
“…Cross-section micrographs of wire and arc additive manufacturing (WAAM) samples with varying process strategies. Previous findings reported in [27,28] have shown the influence of wire feed and welding speed on the height and width of the resulting geometry. It was reported that the wall width increases at higher wire-feed rates and decreases at higher welding speeds, whereas the wire feed shows a dominant influence.…”
Section: Effects On Resulting Geometrymentioning
confidence: 92%
“…Cross-section micrographs of wire and arc additive manufacturing (WAAM) samples with varying process strategies. Previous findings reported in [27,28] have shown the influence of wire feed and welding speed on the height and width of the resulting geometry. It was reported that the wall width increases at higher wire-feed rates and decreases at higher welding speeds, whereas the wire feed shows a dominant influence.…”
Section: Effects On Resulting Geometrymentioning
confidence: 92%
“…Fang et al [32], on the other side, measured a relatively low area percentage (0.36-0.85%) in AA5183 thin walls. Köhler et al [33] compared the porosity content of AA5356 and AA4047 by visual inspection (no statistical data was given), and concluded AA5356 being denser. However, porosity is dependent on a wide range of parameters, such as deposition mode (GMAW/GTAW), wire quality, input deposition parameters and possibly component design (thin wall versus block).…”
Section: Microstructurementioning
confidence: 99%
“…Детали из сплава АК12 зачастую используют в качестве поршней двигателей, картеров двигателей автомобилей или автомобильных узлов [5][6][7][8][9]. На сегодняшний день уже исследованы изделия с использованием аддитивных технологий из сплава Al-12Si преимущественно в работах методом селективного лазерного плавления [8][9][10], но встречается и в работах с применением дуговой проволочной аддитивной технологией [11]. Из-за высокой отражательной способности лазера и из-за высокой пористости, получаемых дуговой аддитивной технологией изделий, стоит перейти к методу электронно-лучевого плавления.…”
Section: институт физики прочности и материаловедения со ран томскunclassified